Development of a loop-mediated isothermal amplification method for detecting virulent Rhodococcus equi. (September 2016) - Kinoshita, Yuta; Niwa, Hidekazu; Higuchi, Tohru; Katayama, Yoshinari
Rhodococcus equi is the most important causative bacterium of severe pneumonia in foals. We report herein the development of a specific loop-mediated isothermal amplification (LAMP) assay, which targets a gene encoding vapA for detecting virulent R. equi . The detection limit of the LAMP assay was 10 4 colony forming units (CFU)/mL, which was equal to 10 CFU/reaction. The clinical efficacy of the LAMP assay was compared with those of 2 published PCR-based methods: nested PCR and quantitative real-time (q)PCR. Agreements between bacterial culture, which is the gold standard for detection of R. equi, and each of the 3 molecular tests were measured by calculating a kappa coefficient. The kappa coefficients of the LAMP (0.760), nested PCR (0.583), and qPCR (0.888) indicated substantial agreement, moderate agreement, and almost perfect agreement, respectively. Although the clinical efficacy of LAMP was not the best among the 3 methods tested, LAMP could be more easily introduced into less well-equipped clinics because it does not require special equipment (such as a thermocycler) for gene amplification. Veterinary practitioners could diagnose R. equi pneumonia more quickly by using LAMP and could use the results to select an appropriate initial treatment.